Psychometric properties of early childhood development assessment tools in low- and middle-income countries: a systematic review - Bliznashka, Lilia; Hentschel, Elizabeth; Ali, Nazia Binte; Hunt, Xanthe; Neville, Sarah Elizabeth; Olney, Deanna K.; Pitchik, Helen O.; Roy, Aditi; Seiden, Jonathan; Solís-Cordero, Katherine; Thapa, Aradhana; Jeong, Joshua (BMJ, 2025)
Objective Valid and reliable measurement of early childhood development (ECD) is critical for monitoring and evaluating ECD-related policies and programmes. Although ECD tools developed in high-income countries may be applicable to low- and middle-income countries (LMICs), directly applying them in LMICs can be problematic without psychometric evidence for new cultures and contexts. Our objective was to systematically appraise available evidence on the psychometric properties of tools used to measure ECD in LMIC.